Foot area and height of centre of gravity of individuals as determinants during the transition phase of step and jump of triple jumping - Venkata, R K (British journal of sports medicine, 2010)
Larger foot area and lower centre of gravity need more propulsive force. Larger foot area releases larger amount of force into the earth causing ineffective repulsion during the step and jump phases making more uneconomical. This study was to analyse the correlation among the area of the foot, height of the individual and step and jump performance of triple jumping. Foot area of the 200 subjects was measured by graph weighing method. The mean subject height was 170 cm: all were nonobese without any prior regular athletic training. Partial correlation was applied to analyse the correlation between the distance achieved for step and jump phases and foot area, centre of gravity height of the participants. A significant negative correlation was found between foot area and the performance (r=−0.148; p<0.003), but no significant correlation was found between height and the performance. The negative correlation between foot area and the performance was greater (r=−0.191; p<0.0001), when the effect of height was removed through first order partial correlation. The positive correlation between height and performance was found increased to significant level (r=0.142; p<0.0014), when the effect of foot area was removed through partial correlation of first order. The performance of step and jump phases of triple jump decreases with the increase in the area of the foot and increases with the increase in height of centre of gravity of individuals.